การศึกษาพฤติกรรมการดูแลช่วยเหลือนักเรียนที่มีพฤติกรรมก้าวร้าว ของครูโรงเรียนศรีอยุธยา ในพระอุปถัมภ์ฯ - นามสีลี, วิชรัชต์; กุโลภาส, ธีรภัทร (An Online Journal of Education, 2018)
The purposes of this descriptive research were to 1) study teachers’ behaviors level in supporting aggressive students in Sriayudhya school. 2) Compare teacher’s behaviors and aggressive students’ behaviors distinguished by sex, class level, and experience. 3) Study correlation between teachers’ behaviors in supporting aggressive students and teachers’ perception on the severity of problems of aggressive students. 4) Compare between teachers’ experience with teachers’ perception on severity of problems of aggressive students. Population is 129 teachers of Sriayudhya school in year 2015. The research tool was questionnaire. Data were analyzed by frequency, percentage, mean, S.D, t-test, ANOVA and content analysis. The findings showed that 1) the overall and every aspect of teachers’ behaviors in supporting aggressive students were high. 2) Gender, class level, and experience of teachers have no relation with teachers’ behaviors in supporting aggressive students. 3) No correlation between teachers’ behaviors in supporting aggressive students and teachers’ perception on severity of problems of aggressive students. 4) Teachers’ experience correlated with teachers’ perception on severity of problems of aggressive students. The result was statistically significant at.05. Teachers who have more than 15 years experience have less perception on severity of problems of aggressive students than teachers who have less than 5 years experience.